2022
DOI: 10.1111/1467-9655.13867
|View full text |Cite
|
Sign up to set email alerts
|

Faking it or making it: the politics of consumption and the precariousness of social mobility in South Africa

Abstract: This article critically explores the complex and contradictory meanings attached to conspicuous consumption in an informal settlement on the outskirts of Johannesburg. It examines why un(der)employed young people, especially young Black men, view the trappings of wealth in their midst and dismiss them as ‘fake’. The article shows how the widespread concern with ‘faking it’ indexes the unstable links between consumption, status, and class differentiation in a time of generalized economic insecurity. Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Ferguson 1999: 82–6). Hannah Dawson’s (2023) research in urban South Africa has shown how discourses about ‘fake’ wealth reflect the image of success made possible by conspicuous consumption – having a Mercedes-Benz car, for instance – and the way in which aspiration itself is thought of in terms of a material culture of display (cf. Newell 2012).…”
mentioning
confidence: 99%
“…Ferguson 1999: 82–6). Hannah Dawson’s (2023) research in urban South Africa has shown how discourses about ‘fake’ wealth reflect the image of success made possible by conspicuous consumption – having a Mercedes-Benz car, for instance – and the way in which aspiration itself is thought of in terms of a material culture of display (cf. Newell 2012).…”
mentioning
confidence: 99%